2012
DOI: 10.5194/os-8-419-2012
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Ross Sea Bottom Water changes on the warming and freshening of the Antarctic Bottom Water in the Australian-Antarctic Basin

Abstract: Abstract. Changes to the properties of Antarctic BottomWater in the Australian-Antarctic Basin (AA-AABW) between the 1990s and 2000s are documented using data from the WOCE Hydrographic Program (WHP) and repeated hydrographic surveys. Strong cooling and freshening are observed on isopycnal layers denser than γ n = 28.30 kg m −3 . Changes in the average salinity and potential temperature below this isopycnal correspond to a basin-wide warming of 1300 ± 200 GW and freshening of 24 ± 3 Gt year −1 . Recent changes… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
32
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 40 publications
5
32
0
Order By: Relevance
“…The likely influence of freshened dense shelf water from the Ad elie Land sector is also consistent with the freshening of 0.03 identified over approximately the same period (1992)(1993)(1994)(1995)(1996)(1997)(1998)(1999)(2000)(2001)(2002)(2003)(2004) in the AAB bottom layer at 140 E on the continental slope just downstream of the Ad elie Land shelf [Aoki et al, 2005]. Although Shimada et al [2012] have recently suggested that a large (84%) part of the overall AAB freshening could be explained by observed changes in the transport and properties of the RSBW, they acknowledge that localized cooling (as opposed to basin wide warming) and enhanced freshening signals identified over the slope near the ALBW source region do indicate the influence of a fresher, colder, bottom water source there.…”
Section: Introductionsupporting
confidence: 75%
See 3 more Smart Citations
“…The likely influence of freshened dense shelf water from the Ad elie Land sector is also consistent with the freshening of 0.03 identified over approximately the same period (1992)(1993)(1994)(1995)(1996)(1997)(1998)(1999)(2000)(2001)(2002)(2003)(2004) in the AAB bottom layer at 140 E on the continental slope just downstream of the Ad elie Land shelf [Aoki et al, 2005]. Although Shimada et al [2012] have recently suggested that a large (84%) part of the overall AAB freshening could be explained by observed changes in the transport and properties of the RSBW, they acknowledge that localized cooling (as opposed to basin wide warming) and enhanced freshening signals identified over the slope near the ALBW source region do indicate the influence of a fresher, colder, bottom water source there.…”
Section: Introductionsupporting
confidence: 75%
“…Several studies have reported significant changes in the properties of the AABW in the Australian Antarctic Basin during the past decades [Whitworth, 2002;Aoki et al, 2005;Rintoul, 2007;Johnson et al, 2008;Shimada et al, 2012]. As often stated, such changes may just reflect changes in the properties or proportion of ambient water entrained or mixed with the source waters along their path across the basin.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Rhein et al, (2013); data from Purkey and Johnson (2010) Linear trends of deep ocean change, constructed from repeat sections between 1992 and 2005, reveal that most of the abyssal ocean is warming, with strongest warming close to Antarctica (Figures 1 and 4c; Purkey and Johnson, 2010;Rhein et al, 2013;Talley et al, 2016). The abyssal waters are also contracting in volume and freshening Johnson, 2012, 2013;Shimada et al, 2012;Jullion et al, 2013;van Wijk and Rintoul, 2014). The observed bottom water changes reflect the responses of bottom water source regions to changes in surface climate, to ocean-ice shelf interaction, and to downstream propagation of the signals by wave and advective processes (Jacobs and Giulivi, 2010;Masuda et al, 2010;Johnson et al, 2014;van Wijk and Rintoul, 2014).…”
Section: Observed Temperature Trendsmentioning
confidence: 99%